Sympathetic innervation in skeletal muscle and its role at the neuromuscular junction - Rudolf, Rüdiger; Kettelhut, Isis Do Carmo; Navegantes, Luiz Carlos Carvalho (Journal of muscle research and cell motility, 2024)
Neuromuscular junctions are the synapses between motor neurons and skeletal muscle fibers, which mediate voluntary muscle movement. Since neuromuscular junctions are also tightly associated with the capping function of terminal Schwann cells, these synapses have been classically regarded as tripartite chemical synapses. Although evidences from sympathetic innervation of neuromuscular junctions was described approximately a century ago, the essential presence and functional relevance of sympathetic contribution to the maintenance and modulation of neuromuscular junctions was demonstrated only recently. These findings shed light on the pathophysiology of different clinical conditions and can optimize surgical and clinical treatment modalities for skeletal muscle disorders.
Gesehen am 22.04.2024